Mutator/Hypermutable Fetal/Juvenile Metakaryotic Stem Cells and Human Colorectal Carcinogenesis - Kini, Lohith G.; Herrero-Jimenez, Pablo; Furth, Emma E.; Kamath, Tushar; Sanghvi, Jayodita; Gutierrez, Efren; Hensle, David; Kogel, John; Kusko, Rebecca; Rexer, Karl; Kurzweil, Ray; Refinetti, Paulo; et al. (Frontiers in Oncology, 2013)
Adult age-specific colorectal cancer incidence rates increase exponentially from maturity, reach a maximum, then decline in extreme old age. Armitage and Doll (1957) postulated that the exponential increase resulted from “n” mutations occurring throughout adult life in normal “cells at risk” that initiated the growth of a preneoplastic colony in which subsequent “m” mutations promoted one of the preneoplastic “cells at risk” to form a lethal neoplasia. We have reported cytologic evidence that these “cells at risk” are fetal/juvenile organogenic, then preneoplastic metakaryotic stem cells. Metakaryotic cells display stem-like behaviors of both symmetric and asymmetric nuclear divisions and peculiarities such as bell shaped nuclei and amitotic nuclear fission that distinguish them from embryonic, eukaryotic stem cells. Analyses of mutant colony sizes and numbers in adult lung epithelia supported the inferences that the metakaryotic organogenic stem cells are constitutively mutator/hypermutable and that their contributions to cancer initiation are limited to the fetal/juvenile period. We have amended the two-stage model of Armitage and Doll and incorporated these several inferences in a computer program CancerFit v.5.0. We compared the expectations of the amended model to adult (15-104 yr) age-specific colon cancer rates for European American males born 1890-99 and observed remarkable concordance. When estimates of normal colonic fetal/juvenile APC and OAT gene mutation rates (~2-5 x 10-5 per stem cell doubling) and preneoplastic colonic gene loss rates (~ 8 x 10-3) were applied, the model was in accordance only for the values of n = 2 and m = 4 or 5.